ANALISIS KINERJA VOIP SERVER PADA WIRELESS ACCESS POINT - , Effan Najwaini ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Voice quality on VoIP (Voice Over IP) communication is caused by many factors, one of which is the quality of the server. Choosing PC platform or server which is suitable (both of price and performance) is the main issue in developing VoIP network. A bad server performance or not equivalent with the most of users will degrade the sound quality or even not able to connect between users. In this study, the test carried out to the performance of the wireless access point Linksys WRT54GL which is used as a VoIP server. The test was carried out to determine how many VoIP calls which are able to be serviced by a wireless access point as a VoIP server and how long the server needs to be able to process every signal of SIP and RTP packet. This study will also compare the server performance over the media handling methods of the server. Based on the test result performed, the VoIP server on the wireless access point is able to serve VoIP communication well for a few calls number, so it is worth to be implemented on the use of small scale. The use of Native Bridging method in handling the media performed by the server can increase the number of calls that were able to be served about 3 to 7 times compared with other methods